2016
DOI: 10.1039/c5cp07752d
|View full text |Cite
|
Sign up to set email alerts
|

Photo-degradation in air of the active layer components in a thiophene–quinoxaline copolymer:fullerene solar cell

Abstract: We have studied the photo-degradation in air of a blend of [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) and poly[2,3-bis-(3-octyloxyphenyl)quinoxaline-5,8-diyl-alt-thiophene-2,5-diyl] (TQ1), and how the photo-degradation affects the solar cell performance. Using near-edge X-ray absorption fine structure (NEXAFS) spectroscopy, changes to the electronic structure of TQ1 and PCBM caused by illumination in ambient air are investigated and compared between the pristine materials and the blend. The NEXAFS spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…An exception is the exposure time of 2 hours, where there is no significant development of photo-oxidation products in the blend spectra. This means that the presence of the TQ1 does not accelerate the photodegradation of PC 70 BM, which is different from the case of TQ1:PC 60 BM blends, where Hansson et al 27 found by NEXAFS that the PC 60 BM in the TQ1:PC 60 BM blend films degraded more rapidly than a pure PC 60 BM film. After exposure times longer than 2 hours, the blend spectrum develops increased absorption in the carbonyl region, to which both the photo-oxidation of TQ1 and the photo-oxidation of PC 70 BM contribute.…”
Section: Photo-oxidation Of Active Layer Materialsmentioning
confidence: 70%
See 4 more Smart Citations
“…An exception is the exposure time of 2 hours, where there is no significant development of photo-oxidation products in the blend spectra. This means that the presence of the TQ1 does not accelerate the photodegradation of PC 70 BM, which is different from the case of TQ1:PC 60 BM blends, where Hansson et al 27 found by NEXAFS that the PC 60 BM in the TQ1:PC 60 BM blend films degraded more rapidly than a pure PC 60 BM film. After exposure times longer than 2 hours, the blend spectrum develops increased absorption in the carbonyl region, to which both the photo-oxidation of TQ1 and the photo-oxidation of PC 70 BM contribute.…”
Section: Photo-oxidation Of Active Layer Materialsmentioning
confidence: 70%
“…31,45 The pure TQ1 films photobleach rapidly under simulated sunlight in ambient air, which is seen by the decrease in intensity of both absorption bands. 27,46 However, in Fig. 5b, it can be seen that the photobleaching of the TQ1 : PC 70 BM (1 : 3) blend film in the 500-700 nm range is moderate compared to that of the pure TQ1 film.…”
Section: External Quantum Efficiency (Eqe) and Uv-vis Absorption Specmentioning
confidence: 93%
See 3 more Smart Citations